Dietary and Probiotic Influences on Acne: A Comprehensive Review - Religa, Aleksandra; Starzyk, Agnieszka; Charzewski, Piotr; Wrona, Julia (Quality in Sport, 2025)
Acne vulgaris remains a common dermatological disorder among adolescents and adults, posing persistent therapeutic challenges despite continued advancements in treatment. This review synthesizes research conducted between 2014 and 2021, focusing on the contributions of diet, probiotic supplementation, and the gut-brain axis to acne pathogenesis and management. An examination of studies from databases such as PubMed and Scopus indicates that high consumption of carbohydrates and dairy products is associated with increased acne severity, whereas diets rich in omega-3 fatty acids and characterized by a low glycemic index may confer protective effects. Furthermore, probiotics—particularly Lactobacillus and Bifidobacterium strains—exhibit immunomodulatory capacities that may attenuate systemic inflammation and enhance skin barrier function, thereby improving acne outcomes. The gut-brain axis underscores the systemic interconnections between gut health and cutaneous conditions, suggesting that targeted probiotic modulation of this axis could positively influence acne severity. Collectively, these findings emphasize the importance of an integrative strategy for acne management, incorporating both dietary interventions and probiotic supplementation, and underscore the necessity of further research to optimize therapeutic efficacy and promote better patient quality of life.